2017
DOI: 10.1186/s12971-017-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in pregnancy: a cross-sectional study in China

Abstract: BackgroundFindings on smoking among pregnant women were mostly from high income countries and were rarely from China. This study aimed to estimate the prevalence of smoking and its influencing factors among pregnant women living in China.MethodsA cross-sectional analysis was conducted in this study. Data from pregnant women were collected in this study from June to August 2015 from 5 provinces of mainland China. A total of 2345 pregnant women were included in this study, the mean age of the participants was 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
4
25
1
2
Order By: Relevance
“…A study that correlated smoking with socioeconomic conditions in Canadian women showed that a low family income has a strong relation with smoking when compared to women with high family income (18) . A study of factors associated with maintenance of smoking during pregnancy with Chinese women showed that the lower the schooling, the greater the chances of the woman remaining smoking during pregnancy (19) . According to a study conducted in Brazil, a high educational level of the pregnant woman and her partner is more prone to free cigarette families.…”
Section: Discussionmentioning
confidence: 99%
“…A study that correlated smoking with socioeconomic conditions in Canadian women showed that a low family income has a strong relation with smoking when compared to women with high family income (18) . A study of factors associated with maintenance of smoking during pregnancy with Chinese women showed that the lower the schooling, the greater the chances of the woman remaining smoking during pregnancy (19) . According to a study conducted in Brazil, a high educational level of the pregnant woman and her partner is more prone to free cigarette families.…”
Section: Discussionmentioning
confidence: 99%
“…23 The Chinese version of the Family APGAR has demonstrated good test-retest reliability (0.91). 24 This questionnaire also covers the following areas: (1) whether participants have attended prenatal education and received advice regarding smoking cessation from health care professionals at a clinic, (2) smoking and quitting behaviors before and after the partner became pregnant, (3) intention to quit smoking, (4) knowledge about the health hazards of tobacco use to smokers themselves, pregnant women, fetuses, and newborns, (5) attitude toward tobacco use, (6) and risk perception toward smoking using a binary scale (yes or no).…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…A study involving 2,345 pregnant women in ve Chinese provinces found that 40% of expectant fathers still smoked during their partner's pregnancy, and the percentage even increased to 43.79% after their child was born. 4 Another study of 1181 non-smoking Chinese pregnant women found that 75.1% lived with smoking partner and were regularly exposed to SHS. 5 To promote the health of smoking expectant fathers and especially to protect pregnant women and newborns from exposure to SHS, it is vital for health care professionals to implement interventions to help expectant fathers quit smoking.…”
Section: Introductionmentioning
confidence: 99%
“…We excluded questions with too many options (15 options exist on question 10). We also excluded questions that would not have a direct effect on maternal smoking behavior (13)(14)(15)(16), based on previous studies [7,[9][10][11][12][13][14][17][18][19][20][21][22][23][24][25][26][27][28]. Finally, we selected 9 questions (1-9) as individual variables.…”
Section: Exposure Variablesmentioning
confidence: 99%